Decreased Electroencephalography Global Field Synchronization in Slow-Frequency Bands Characterizes Synaptic Dysfunction in Amnestic Subtypes of Mild Cognitive Impairment - Smailovic, Una; Ferreira, Daniel; Ausén, Birgitta; Ashton, Nicholas James; Koenig, Thomas; Zetterberg, Henrik; Blennow, Kaj; Jelic, Vesna (Frontiers in Aging Neuroscience, 2022)
Background: Mild cognitive impairment (MCI) is highly prevalent in a memory clinic setting and is heterogeneous regarding its clinical presentation, underlying pathophysiology and prognosis. Most prevalent subtypes are single domain amnestic MCI (sd-aMCI), considered to be a prodromal phase of Alzheimer’s disease (AD), and multidomain amnestic MCI (md-aMCI) which is associated with multiple etiologies. Since synaptic loss and dysfunction are the closest pathoanatomical correlates of AD-related cognitive impairment, we aimed to characterize it in sd-aMCI and md-aMCI patients by means of resting state EEG global field power (GFP), global field synchronization (GFS) and novel cerebrospinal fluid (CSF) synaptic biomarkers. Methods: We included 52 patients with sd-aMCI (66.97.3 years old, 52% women) and 30 with md-aMCI (63.17.1 years old, 53% women). All patients underwent a detailed clinical assessment, resting state EEG recordings and quantitative analysis (GFP and GFS in delta, theta, alpha, and beta bands) and analysis of CSF biomarkers of synaptic dysfunction, neurodegeneration, and AD-related pathology. MMSE was selected as an estimation of global cognitive performance. All these measures were included in a multivariate model to investigate differences between sd-aMCI and md-aMCI. Results: sd-aMCI patients had higher CSF phosphorylated tau, total tau and neurogranin levels, and lower values in GFS delta and theta. No differences were observed in GFP. The multivariate model showed that the most important synaptic measures for group separation were GFS theta, followed by GFS delta, GFP theta, CSF neurogranin and GFP beta. Conclusion: sd-aMCI patients when compared to those with md-aMCI have neurophysiological and biochemical profile of synaptic damage, neurodegeneration and amyloid pathology closer to that described in AD patients. The most prominent signature in sd-aMCI was a decreased global synchronization in slow frequency bands indicating that functional connectivity in slow frequencies is more specifically related to early effects of AD specific molecular pathology.